Training zones revisited - Maglischo, E. W. (Journal of Swimming Research, 2012)
The purpose of this paper will be to describe a different interpretation of training zones,onethat is based on training the three muscle fiber types. The physiological rationale for this theory was presented in an earlier paper. This follow-up to that paper goes into greater detail concerning how to administer training according to the theory.